2018
DOI: 10.1002/2017jc013148
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing of Waves Propagating in the Marginal Ice Zone by SAR

Abstract: Wave‐ice interactions are important in high sea state conditions, when waves propagate from the open ocean into the marginal ice zone (MIZ) and the pack ice. In situ observations of waves and wave‐ice interactions can be obtained at a small number of MIZ locations in costly and challenging experiments, whereas remote sensing using satellite RADARSAT‐2 SAR (synthetic aperture radar) images can observe waves throughout the MIZ, in all weather conditions. We present a methodology to retrieve MIZ wave parameters f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
(95 reference statements)
2
16
0
Order By: Relevance
“…The behaviors of ),-./01213 and PSD in Figures 1 and 4 may come from multiple mechanisms. The decrease 360 of ),-./01213 towards the interior ice is in agreement with a similar study in the MIZ (Shen et al, 2018), as well as the lengthening of dominant wave periods commonly reported in many field observations (e.g., Robin, 1963;Wadhams et al, 1988;Marko, 2003;Kohout et al 2014;Collins et al, 2015). The phenomenon is commonly explained by the low pass filter mechanism in literature.…”
Section: Evolution Of Wave Characteristicssupporting
confidence: 91%
“…The behaviors of ),-./01213 and PSD in Figures 1 and 4 may come from multiple mechanisms. The decrease 360 of ),-./01213 towards the interior ice is in agreement with a similar study in the MIZ (Shen et al, 2018), as well as the lengthening of dominant wave periods commonly reported in many field observations (e.g., Robin, 1963;Wadhams et al, 1988;Marko, 2003;Kohout et al 2014;Collins et al, 2015). The phenomenon is commonly explained by the low pass filter mechanism in literature.…”
Section: Evolution Of Wave Characteristicssupporting
confidence: 91%
“…In addition to the ice edge, there is another change of 208 in the clockwise direction along Y 5 475 km. We expect the more dramatic changes in directions are effects of refraction (at the ice edge or due to a change in the ice thickness) (e.g., Shen et al, 2018). The overall pattern of Figure 7.…”
Section: Wave Parametersmentioning
confidence: 95%
“…In addition to the ice edge, there is another change of 20° in the clockwise direction along Y = 475 km. We expect the more dramatic changes in directions are effects of refraction (at the ice edge or due to a change in the ice thickness) (e.g., Shen et al, ). The overall pattern of the wave directions can be explained by the angular spreading of wave energy and can be captured by a numerical wave model without including such a refraction (see Part 2: Figure 9a, Ardhuin et al, ).…”
Section: Processing Of Sar Images In the Mizmentioning
confidence: 99%
“…The spatial evolution of the wave field in off-ice wind conditions is analyzed by (Gemmrich et al, 2018). Other remote sensing data include ice classification from fully polarized SAR data (Shen et al, 2018), and wave and ice floe mapping from airborne LIDAR data (Sutherland & Gascard, 2016).…”
Section: In Situ Observations (R/v Sikuliaq Cruise)mentioning
confidence: 99%